Design and evaluation of screening and self-care (mobile) application for oral and dental problems and emergencies - Sedighe Sadat Hashemikamangar; Aidin Sooratgar; Mina Khayamzadeh; Shayan Momeni; Ali Asghar Safaei; Behnaz Behniafar (Journal of Oral Biology and Craniofacial Research)
Introdution: Although oral and dental diseases may occur in unexpected or even emergency conditions, but some of the diagnosis and treatments can be algorithmically done following some guidelines. The development and implementation of a system that provides users with a record of history and a proposal of required actions can be not only efficiently practical, but also virtually simple. Materials and method: A system made up of web and mobile apps is proposed and evaluated for screening and self-care of oral and dental problems and for providing advice on dental emergencies and therapeutic measures. This system was developed and made available to users under the name of 'Dandanyar'. The data were then collected from Dandanyar users and analyzed based on the selected statistical population for evaluating their satisfaction. Results: The evaluation results showed that more than 90 % of specialists had a positive attitude towards application effectiveness. On the other hand, clients expressed their satisfaction with various aspects of the application in more than 80 % of cases. Conclusion: The importance of using such systems is highlighted in the Covid-19 pandemic condition where certain health protocols must be followed. For instance, people must avoid unnecessary traveling and limit their referrals to medical centers especially dental clinics due to the high volume of aerosols produced during dental treatment procedures.